2022
DOI: 10.1021/acsomega.2c01339
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Barite Scale in Carbonate Formations during the Filter Cake Removal Process

Abstract: The barite scale is one of the most common scales in the oil and gas industry. It can form in the reservoir or precipitate in different production equipment. The formation of such a scale will significantly minimize the capillary diameter of the flow channels and consequently shrink the well productivity. On the other hand, the production of movable barite particles causes severe erosion for the installed equipment. There are several sources of the barite scale such as mixing of incompatible brines and solid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It was also shown that combinations of chelating agents such as DTPA/GLDA, DTPA/EDTA, or DTPA/MGDA resulted in lower performance than DTPA alone. This is mainly because barite dissolution is inhibited by the physical presence of other chelating agent molecules [66,67]. It was also noted that barite dissolution with DTPA increases as temperature increased, indicating a thermally activated process [63,68,69].…”
Section: Chelating Agent Optimum Ph Range For Iron (Iii) (Re-graphed ...mentioning
confidence: 99%
“…It was also shown that combinations of chelating agents such as DTPA/GLDA, DTPA/EDTA, or DTPA/MGDA resulted in lower performance than DTPA alone. This is mainly because barite dissolution is inhibited by the physical presence of other chelating agent molecules [66,67]. It was also noted that barite dissolution with DTPA increases as temperature increased, indicating a thermally activated process [63,68,69].…”
Section: Chelating Agent Optimum Ph Range For Iron (Iii) (Re-graphed ...mentioning
confidence: 99%
“…An important objective is to increase the barite solubility by exploring different chemical systems under various conditions. Several types of chelating agents were proposed to remove the barite deposition including DTPA, GLDA, EDTA, HEDTA, and NTA. , In addition, mixtures of chelating agents and different types of catalysts were studied to improve the barite solubility. ,, The dissolution of barite in aqueous DTPA was enhanced using potassium carbonate, potassium formate, potassium chloride, potassium nitrate, ammonium chloride, ammonium carbonate, sodium carbonate, calcium chloride, and magnesium chloride. ,, The barite solubility can be increased by adjusting the pH, increasing the pH above 12 showed a considerable improvement in the barite solubility because of the higher binding affinity of carboxylates compared to protonated carboxylic acid groups. , 20 wt % DTPA prepared using potassium base salt and with pH above 11 showed barite solubility of around 67% while adding converting agents such as potassium carbonate or potassium chloride led to increasing the solubility to above 90%. ,, The use of converting agents might lead to other types of formation damage due to the incompatibility between the additional additives and the formation. …”
Section: Introductionmentioning
confidence: 99%